2007
DOI: 10.1007/s00109-007-0193-2
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular responses in progressive pseudorheumatoid dysplasia articular cartilage associated with compound heterozygous WISP3 gene mutation

Abstract: Progressive pseudorheumatoid dysplasia (PPD) is characterized by continuous degeneration and loss of articular cartilage, which has been attributed to mutations in the gene encoding WISP3. We collected a PPD family and analyzed their WISP3 genes mutation. Articular chondrocytes (ACs) were purified from the femurs of a PPD patient after hip replacement surgery. Cell growth, proliferation, and viability were examined. Gene expression profiling and analyses of matrix metalloproteinases (MMP)-1, -3, and -13 protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…Subsequently, a total of 18 WISP3 mutations located in exons 2 to 5 have been described in China (Table 1) [2, 7, 8, 1115]. They include five different mutations (two frameshift mutations and one nonsense mutation) located in exons 2 and 3 (two missense mutations), respectively, as well as five mutations in exon 5 (three frameshift mutations, one nonsense mutation and one missense mutation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, a total of 18 WISP3 mutations located in exons 2 to 5 have been described in China (Table 1) [2, 7, 8, 1115]. They include five different mutations (two frameshift mutations and one nonsense mutation) located in exons 2 and 3 (two missense mutations), respectively, as well as five mutations in exon 5 (three frameshift mutations, one nonsense mutation and one missense mutation).…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al found that WISP3 was expressed at low levels in articular cartilage chondrocytes in PPD patients [11], a finding that may explain why PPD mainly affects articular cartilage. However, the pathogenic mechanism of the WISP3 gene in PPD remains unclear; thus, a specific therapy is not yet available [3].…”
Section: Discussionmentioning
confidence: 99%
“…WISP3 gene spans over 5 exons and encodes several functional domains each corresponding to one of the exons. Exon 1 encodes a peptide sequence that plays role in Wisp secretion (7,(10)(11)(12); exon 2 codes for insulin-like growth factor binding proteins (IGFBPs) that contains twelve cysteine residues (7,10,12-15); exon 3 encodes a cysteine rich, von Willebrand factor type C repeat domain (10,11,13,15); exon 4 contains information for a thrombospondin type 1 domain biosynthesis (with six cysteine residues) that may bind to sulfated glycosaminoglycan's either at cell surfaces or in extracellular matrix (11,12,(15)(16)(17)(18); and exon 5 that encodes a cysteine knot domain comprised of ten cysteine residues possibly involved in dimerization and receptor binding (10)(11)(12)(14)(15)(16)(17)(19)(20)(21)(22)(23)(24). Until now, a number of mutations and polymorphisms were found throughout the WISP3 sequence with geographically localized origin ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that WISP3 regulates the expression of type II collagen and aggrecan. They are essential cartilage specific molecules which take part in cartilage integrity (22 (21). It implies that protein's WNT inhibitory function requires proper folding of multiple domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation